Kualitas Pelayanan Publik di Dinas Kependudukan dan Pencatatan Sipil Kabupaten Pohuwato - Aprijal Rajak; Zuchri Abdussamad; Romy Tantu (Kajian Administrasi Publik dan ilmu Komunikasi, 2025)
This study aims to examine the quality of public services at the Population and Civil Registration Office (Disdukcapil) of Pohuwato Regency using the SERVQUAL model, which comprises five dimensions: Tangibles, Reliability, Responsiveness, Assurance, and Empathy. This research was conducted in response to persistent public complaints regarding slow service processes, long queues, limited facilities and infrastructure, network disruptions, as well as insufficient information and uncertainty concerning service completion time. The study employed a descriptive qualitative approach through observation, interviews with Disdukcapil employees and community members, and documentation. The findings indicate that the quality of public services has not yet been optimal. The Tangibles dimension remains weak due to inadequate service facilities. Reliability has not been fully achieved as a result of delays in document issuance and system disruptions. Responsiveness among service officers is inconsistent in addressing public complaints. In terms of Assurance, officers demonstrate adequate professionalism; however, transparency in procedures and service timelines remains inconsistent. Meanwhile, in the Empathy dimension, attention to the community particularly vulnerable groups still needs improvement. Overall, the public services provided by Disdukcapil Pohuwato have not fully met community expectations and require improvements in facilities, staff competence, and the effectiveness of service systems.